Tracked Changes. Plastics piping systems for soil and waste discharge (low and high temperature) within the building structure. Chlorinated poly(vinyl chloride) (PVC-C). Specifications for pipes, fittings and the system Part 1, (8th June 2023) - British Standards Institution,
No abstract available